Konstatering dalam Penanganan Tindak Pidana Kekerasan : Analisis Penerapan Restorative Justice di Polres Kupang Kota - Dede Agusto Fransisco Lubalu (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines the application of konstatering as an effort to realize restorative justice in handling violence cases in Manulai II, Alak District, by the Kupang City Resort Police and identifies the factors affecting its implementation. The study is based on the premise that konstatering serves as an essential legal mechanism for verifying criminal elements and determining whether a case is eligible for settlement through a restorative justice approach while maintaining legal certainty, justice, and public benefit. This research employed an empirical legal method using statutory, conceptual, and case approaches. Primary data were obtained through interviews with investigators, victims, offenders, and community leaders, while secondary data were collected through the analysis of legislation and legal literature. The data were analyzed qualitatively using a descriptive approach. The findings reveal that konstatering provides an objective basis for assessing criminal elements, evidence, and the willingness of the parties to reach reconciliation. In the Manulai II case, restorative justice was successfully implemented because the offender admitted responsibility, the victim voluntarily agreed to reconciliation, losses were restored, and the settlement did not generate public objection. Nevertheless, its implementation is constrained by limited legal regulation concerning konstatering, differences in investigators’ understanding, institutional capacity limitations, and a legal culture that still prioritizes punitive justice. Strengthening legal regulations and improving investigators’ competence are therefore necessary to ensure the consistent and effective implementation of restorative justice.